Experimental Study on the Bearing Performance of Rock-Socketed Concrete-Filled Steel Tube Piles under Horizontal Cyclic Loading - Mingwei Liu; Fayou Wu; Erdi Abi; Linjian Wu; Yafeng Han; Nirui Chen; Jue Chen (Journal of Marine Science and Engineering, 2023)
Rock-socketed concrete-filled steel tube piles (RSCFSTs), which have been widely used in harbors, bridges, and offshore wind turbines, were exposed to horizontal cyclic loading during service and suffered fatigue damage. For the RSCFSTs, longitudinal steel bars were welded to the inner wall of the steel tube to enhance the bonding strength of the steel tube and concrete core interface. It is essential to research the bearing performance of RSCFSTs like this, under horizontal cyclic loading. In this paper, cyclic loading tests of RSCFSTs under horizontal loading were carried out. The failure patterns of RSCFSTs during the destabilization process were generalized, and the lateral displacement development law of RSCFSTs was analyzed. The interfacial bonding characteristics between the steel tube and concrete core during the test were also discussed. Results showed that the horizontal bearing capacity of RSCFSTs decreases nonlinearly with the increase in the equal amplitude of load, and the development process of the lateral displacement-cycle number curve was divided into three phases: (I) rapid growth period, (II) fatigue growth period, and (III) sharp growth period. The larger the horizontal load was, the faster the lateral displacement entered the fatigue growth period. The duration of the rapid growth period and fatigue damage period accounts for about 90% of the total life of RSCFSTs. The stiffening form of the longitudinal steel bars welded to the inner wall of the steel tube can realize the synergistic force between the upper steel tube and the concrete core of RSCFSTs, which accounts for about 7/10 of the length of RSCFSTs. The depth of the steel tube, foundation stiffness, and bonding performance between the steel tube and the concrete core were the key factors that affected the horizontal bearing performance of RSCFSTs. Finally, some constructive suggestions are proposed for the design of RSCFSTs, including increasing steel tube embedded depth, adding a sniffer bar between the steel tube and concrete interface, etc.